PENGARUH LEVERAGE DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL PEMODERASI - Ida Ayu Putu Yuli Muliawati; I Putu Fery Karyada (UNHI Press, 2020)
This study aims to obtain empirical evidence of the effect of leverage and capital intensity on tax aggressiveness with an independent commissioner as a moderating variable. The population of the research is the goods and consumption industry sector manufacturing companies listed on the Indonesia Stock Exchange in 2013-2018. The sample used is purposive sampling. The type of data that is secondary data and the method of analysis used is MRA Analysis. The results of this study indicate that leverage and capital intensity have a positive effect on tax aggressiveness, independent commissioners weaken the relationship between leverage and capital intensity on tax aggressiveness.